Spin and pseudospin symmetries in the antinucleon spectrum of nuclei - Lisboa, R.; Malheiro, M.; Alberto, P.; Fiolhais, M.; De Castro, A. S. [UNESP] (American Physical Society (APS), 2010)
Spin and pseudospin symmetries in the spectra of nucleons and antinucleons are studied in a relativistic mean-field theory with scalar and vector Woods-Saxon potentials, in which the strength of the latter is allowed to change. We observe that, for nucleons and antinucleons, the spin symmetry is of perturbative nature and it is almost an exact symmetry in the physical region for antinucleons. The opposite situation is found in the pseudospin symmetry case, which is better realized for nucleons than for antinucleons, but is of dynamical nature and cannot be viewed in a perturbative way for either nucleons or antinucleons. This is shown by computation of the spin-orbit and pseudospin-orbit couplings for selected spin and pseudospin partners in both spectra. © 2010 The American Physical Society.